Impact of Fed Tapering Announcements on Emerging Markets - Mishra, Prachi (IMF Working Papers; Working Paper, 2014)
This paper analyzes market reactions to the 2013-14 Fed announcements relating to tapering of asset purchases and their relationship to macroeconomic fundamentals and country economic and financial structures. The study uses daily data on exchange rates, government bond yields, and stock prices for 21 emerging markets. It finds evidence of markets differentiating across countries around volatile episodes. Countries with stronger macroeconomic fundamentals, deeper financial markets, and a tighter macroprudential policy stance in the run-up to the tapering announcements experienced smaller currency depreciations and smaller increases in government bond yields. At the same time, there was less differentiation in the behavior of stock prices based on fundamentals.